Ultrastructural analysis of vascular features in cerebral cavernous malformations - (:unkn) unknown (ELSEVIER, 2013)
Objective: Investigation of the structure of vascular malformations highlights the pathogenic mechanisms underlying their clinical behavior. One of the vascular malformations is called cerebral cavernous malformation (CCM). However, the ultrastructural features of the vascular malformations are not defined in detail. Methods: We aimed to investigate the ultrastructural features of CCMs using transmission (TEM), scanning (SEM) electron microscopy, and also immunohistochemistry methods with antibodies against CCM proteins such as CCM2 and CCM3. CCM tissues (n = 6) microsurgically excised from patients for conventional indications. Results: CCM2 and CCM3 were strongly detected in the vascular endothelium. However, there was a very weak immunostaining in stroma. SEM observations revealed that there were ruptures and damages in the luminal endothelium, possibly due to the damage of intercellular junctions. TEM observations also showed a few ruptures and detachments between the endothelium and basal lamina as observed with partially damages and disconnections. The architecture of pericytes showed protrusions and shrinkages. Our results suggest that the thin vessel walls of CCMs were lacking of subendothelial support and intact basal lamina underlying the endothelial cells. Conclusion: This study is so far the first study attempting to show human CCM lesions with SEM. We believe that an understanding of the ultrastructural features of these lesions by light and electron microscopy techniques would help to understand the pathology of these diseases. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Cerebral cavernous malformation; Ultrastructure; TEM; SEM; Immunohistochemistry; CCM2; CCM3; BLOOD-BRAIN-BARRIER; EXPRESSION; RECEPTORS; PROTEINS; VESSELS; KINASES; CCM2